Enantio- and Diastereoselective Syntheses of 3-Hydroxypiperidines through Iridium-Catalyzed Allylic Substitution - Hoecker, Johannes; Rudolf, Georg C.; Bächle, Florian; Fleischer, Steffen; Lindner, Benjamin D.; Helmchen, Günter (European journal of organic chemistry, 2013)
Stereoselective syntheses of 3‐hydroxypiperidines have been developed. Key intermediates are N‐protected allylamines that are prepared by an enantioselective iridium‐catalyzed allylic amination. A subsequent catch and release procedure that involves an epoxidation and base‐mediated elimination yields δ‐lactams that are suitably functionalized to prepare biologically active 3‐hydroxypiperidines. In addition, applications of this method to the total syntheses of deoxymannojirimycin, D‐erythro‐sphingosine, and chiral building blocks of interest for medicinal chemistry are described. Stereoselective syntheses of 3‐hydroxypiperidines are reported. The key reactions are an iridium‐catalyzed allylic amination and a catch and release procedure that consists of a highly diastereoselective epoxidation and a base‐mediated ring opening of the epoxide. This method was applied to the total syntheses of sphingosine, deoxymannojirimycin, and pharmaceutically relevant small molecules.